2021
DOI: 10.1111/ped.14674
|View full text |Cite
|
Sign up to set email alerts
|

The effects of valproate on serum leptin, insulin, and lipid levels in epileptic children

Abstract: Background Weight gain is an important adverse effect of valproate (VPA) therapy. A number of mechanisms have been proposed for its pathophysiology. The aim of the present study is the evaluation of insulin, leptin and lipid levels in epileptic children on treatment with VPA. Methods Thirty epileptic children treated with VPA, and 20 age–sex‐matched healthy children, were enrolled in this study. Blood samples were taken and the body mass index was calculated for all of the subjects. Serum insulin, leptin, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…A total of 13 publications, involving 1,489 subjects (case group: 477, control group: 1012) [10, 1216, 18, 2025], summarized the effects of VPA monotherapy on TG levels in children with epilepsy. No significant heterogeneity ( p = 0.05, I 2 = 42%) was observed; therefore, we used a fixed‐effects model to conduct the meta‐analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 13 publications, involving 1,489 subjects (case group: 477, control group: 1012) [10, 1216, 18, 2025], summarized the effects of VPA monotherapy on TG levels in children with epilepsy. No significant heterogeneity ( p = 0.05, I 2 = 42%) was observed; therefore, we used a fixed‐effects model to conduct the meta‐analysis.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 15 articles [10,[12][13][14][15][16][17][18][19][20][21][22][23][24][25], involving 1,649 subjects (case group: 506, control group: 1143), summarized the effects of VPA monotherapy on HDL levels in children with epilepsy. There was heterogeneity (p<0.00001, I 2 =82%), but the cause of heterogeneity was not detected by subgroup analysis.…”
Section: Vpa and Hdl-cmentioning
confidence: 99%
“…This study demonstrated higher leptin levels in the patient group despite similar BMI values. Hence, it seems likely that VPA causes leptin resistance [28].…”
mentioning
confidence: 99%